2018
DOI: 10.3201/eid2411.181274
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of African Swine Fever Virus, China, 2018

Abstract: On August 3, 2018, an outbreak of African swine fever in pigs was reported in China. We subjected a virus from an African swine fever–positive pig sample to phylogenetic analysis. This analysis showed that the causative strain belonged to the p72 genotype II and CD2v serogroup 8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
293
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(304 citation statements)
references
References 6 publications
(10 reference statements)
8
293
0
3
Order By: Relevance
“…Also, this strain has the characteristic of the intergenic region (IGR) II variant of genotype II group, which has an additional tandem repeat sequence (5'‐GGAATATATA‐3') between the I73R and I329L. The IGR II variant is identical to those observed in Ukr12/Zapo, Lt14/1490, Pol14/Krus (Gallardo et al, ), and China strains (SY18 and CN201801) (Ge et al, ). We compared the nucleotide sequences of p72 and p54 of Korea/Pig/Paju1/2019 with those of Georgia 2007/1, SY18/China/2018, AnhuiXCGQ/China/2018 and VNUA/HY/Vietnam (GenBank accession nos.…”
mentioning
confidence: 84%
“…Also, this strain has the characteristic of the intergenic region (IGR) II variant of genotype II group, which has an additional tandem repeat sequence (5'‐GGAATATATA‐3') between the I73R and I329L. The IGR II variant is identical to those observed in Ukr12/Zapo, Lt14/1490, Pol14/Krus (Gallardo et al, ), and China strains (SY18 and CN201801) (Ge et al, ). We compared the nucleotide sequences of p72 and p54 of Korea/Pig/Paju1/2019 with those of Georgia 2007/1, SY18/China/2018, AnhuiXCGQ/China/2018 and VNUA/HY/Vietnam (GenBank accession nos.…”
mentioning
confidence: 84%
“…After its spread from eastern Africa to Georgia in 2007, ASF has become more prevalent in the Caucasus region, further spread in Russian Federation, and then progressively affected the eastern Europe, including Ukraine (2012), Belarus (2013), Lithuania (2014), Estonia (2014), Poland (2014), Latvia (2014), Romania (2017), the Czech Republic (2017) and Hungary (2018). In 2018, ASF spread into China (Ge et al., ) and Belgium (Linden et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in July 2018, an outbreak of ASF was reported for the first time in China and is still ongoing. The molecular characterization of outbreak samples showed that isolates belong to genotype II (Ge et al., ). Similarly, in September 2018, Belgium reported ASF in two wild boars near the village of Etalle in the province of Luxembourg caused by isolates belonging to genotype II (Garigliany et al., ).…”
Section: Introductionmentioning
confidence: 99%